Sri Aurobindo and the Mother : an introduction - Pandit, Madhav Pundalik, 1918- (Dipti Publications, 1975)
On Aurobindo Ghose, 1872-1950, Indian philosopher, and La Mère, 1878-1973, a leader of the Sri Aurobindo Ashram in Pondichery; radio talks.